The joint decision of female labour supply and childcare in Italy under costs and availability constraints - Francesco Figari; Edlira Narazani (University of Essex, Institute for Social and Economic Research (ISER), 2017)
It is widely recognized that childcare has important pedagogical, economic and social effects on both children and parents. This paper is the first attempt to estimate a joint structural model of female labour supply and childcare behaviour applied to Italy in order to analyse the effects of relaxing the existing constraints in terms of childcare availability and costs by considering public, private and informal childcare. Results suggest that Italian households might alter their childcare and labour supply behaviours substantially if the coverage rate of formal childcare increases to reach the European targets. Overall, increasing child care coverage is estimated to be more effective in enhancing labour incentives than decreasing existing child care costs, at the same budgetary cost.
Keywords: H53; J13; J22; I38; 330; childcare; female labour market participation; labour supply; Italy; microsimulation; EUROMOD